Phase transition and proton ordering at 50 K in 3‐(pyridin‐4‐yl)pentane‐2, 4‐dione. Issue 6 (11th December 2017) - Truong, Khai-Nghi; Merkens, Carina; Meven, Martin; Faßbänder, Björn; Dronskowski, Richard; Englert, Ulli
Abstract : At ambient temperature, the H atom in the short intramolecular hydrogen bond of 3‐(pyridin‐4‐yl)pentane‐2, 4‐dione is disordered; below 50 K, a structural phase transition and proton ordering are observed. Abstract : Single‐crystal neutron diffraction experiments at 100 and 2.5 K have been performed to determine the structure of 3‐(pyridin‐4‐yl)pentane‐2, 4‐dione (HacacPy) with respect to its protonation pattern and to monitor a low‐temperature phase transition. Solid HacacPy exists as the enol tautomer with a short intramolecular hydrogen bond. At 100 K, its donor···acceptor distance is 2.450 (8) Å and the compound adopts space group C 2/ c, with the N and para ‐C atoms of the pyridyl ring and the central C of the acetylacetone substituent on the twofold crystallographic axis. As a consequence of the axial symmetry, the bridging hydrogen is disordered over two symmetrically equivalent positions, and the carbon–oxygen bond distances adopt intermediate values between single and double bonds. Upon cooling, a structural phase transition to the t 2 subgroup P occurs; the resulting twins show an ordered acetylacetone moiety. The phase transition is fully reversible but associated with an appreciable hysteresis in the large single crystal under study: transition to the low‐temperature phase requires several hours at 2.5 K and heating to 80 K is required to revert the transformation. No significant hysteresis is observed in a powder sample, in agreement with the second‐order nature of the phase transition.